A [K, KL] Sector-Based Hands-Off Control with Quantization Parameter Mismatch - Sachan A.; Mahto S.C.; Singh V.K.; Kamal S.; Dinh T.N. (My University, 2025)
A Hands-off control law is investigated to asymptotically stabilize a nonlinear system with input-quantization. The quantization parameters generated at the coder and decoder sides of the communication channel are mismatched and a time-varying ratio is modeled to show the non-synchronous adjustment of the quantization parameters. By the means of [K,KL] sector, the state-space is roughly divided into an attractive and non-attractive regions and a controller based on On-Off logic is utilized to remove the model uncertainties caused by the mismatch of the quantization parameters with limited control effort. Finally, the illustration of the proposed scheme is verified for an electronic circuit. © 2004-2012 IEEE.